(untitled) (Fiep Bulletin - online, 2011)
It was analyzed the effect of the direction of interlateral transfer of learning in dart throwing task. Forty children (10 to 12 years old), divided into two groups GP-Np and GNp-P, performed the task of throwing darts aimed to a spatial target. GP-Np group performed the tests with the preferred hand and the acquisition phase with the non-preferred hand and the GNp-P group performed the tests with the non-preferred hand and the acquisition phase with the preferred hand. Groups performed a pretest (10 trials), acquisition phase (100 trials) and posttest (10 trials). The absolute error was calculated considering the center of the target. Interlateral transfer of learning was not found. This absence of interlateral transfer of learning was explained by the small amount of practice provided during the acquisition phase. Thus, interlateral transfer of learning will occurred just when a significant amount of practice is provided improving the performance of the side that practices. Because, only part of the elements acquired as a result of the specific practice from one of the sides is transferred for the other side. Also, it is suggested that the greater the number of the perceptual-motor elements in the task, the greater will be the chances of the interlateral transfer of learning to happen.